IMPLEMENTATION OF INVENTORY MANAGEMENT AND USE OF GOODS IN THE REGIONAL FINANCE AND ASSETS OFFICE OF WEST KALIMANTAN PROVINCE - Andra Gustiayu Pratiwi; Pudjianto; Ida Rochmawati (RADJA PUBLIKA, 2025)
This study aims to implement inventory management and use of goods determined by factors namely organization, understanding and application at the Regional Asset Finance Office (RAFO) of West Kalimantan Province. The background of this study is based on the importance of inventory management and use of regional goods, because there are still several regional devices that have not submitted regional goods administration reports, maintenance of damaged goods is not optimal, procurement of goods is not in accordance with Regional Asset Needs Plan (RANP) and does not comply with regional asset management standards and inventory of goods that have no reporting administration. The study uses a qualitative descriptive approach with a naturalistic research method from Charles O. Jones to assess the organization, understanding and application in the management and use of regional goods. Data collection techniques include observation, documentation, and in-depth interviews with goods administrators and employees of the Regional Asset Finance Office of West Kalimantan Province. The results of the study indicate that firstly the implementation of inventory management and use of goods at the Regional Asset Finance Office of West Kalimantan Province as a whole has been running well and in accordance with the rules, namely starting from the registration and recording of regional assets, asset management through information systems and supervision and control has followed the above procedures and utilized the existing information system, RAFO of West Kalimantan Province strives to ensure effective, efficient, transparent and accountable management of regional assets. Secondly, the factors in inventory management and use of goods at the Regional Asset Finance Office of West Kalimantan Province include several aspects, including the lack of competent human resources, minimal understanding of regulations, the lack of integrated information systems, budget limitations, discipline in recording and reporting and lack of supervision and evaluation. Suggestions that can be given are in the form of improving the quality of human resources through technical guidance and training.